Pemberian Social Support Dalam Bentuk Pemberian Motivasi Kepada Pasien Rehabilitasi Narkoba - Oktariani; Arbana Syamantha; Evri Ekadiansyah (Forum Kerjasama Pendidikan Tinggi, 2021)
Drug abuse among the community is an act that is not in accordance with social norms and values that apply in society. For victims of drug abuse, serious and thorough treatment is needed. It means that the victim can be aware and not relapse into the problem of drug abuse. The purpose of this community service activity is to provide social support in the form of providing motivation to Drug Rehabilitation Patients. This community service activity is in the form of psychoeducation, which is a form of providing social support with this activity, it is hoped that drug rehabilitation patients can motivate themselves to look to a better future after they leave or finish undergoing a program at a drug rehabilitation center. This activity is in the form of a seminar on providing Social Support in the form of providing motivation to Drug Rehabilitation Patients, which is attended by Drug Rehabilitation Patients at Al Kamal Sibolangit Center. Providing social support in the form of motivation for drug rehabilitation patients is expected to reduce anxiety levels. Individuals who lack or even do not have social support have high levels of anxiety. For this reason, support is needed so that individuals can share their problems with people around whom they trust, are able to change their views or perceptions regarding the events experienced, with social support, individuals who have problems can exchange ideas with other people who can change their views on the problem. experienced and can also affect responses related to the events experienced